2017
DOI: 10.1007/s00709-017-1133-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of knockout of At4g20990 gene encoding α-CA4 on photosystem II light-harvesting antenna in plants grown under different light intensities and day lengths

Abstract: Effect of knockout of the At4g20990 gene encoding α-carbonic anhydrase 4 (α-CA4) in Arabidopsis thaliana in plants grown in low light (LL, 80 μmol photons m s) or in high light (HL, 400 μmol photons m s) under long (LD, 16 h) or short (SD, 8 h) day length was studied. In α-CA4 knockout plants, under all studied conditions, the non-photochemical quenching was lower; the decrease was more pronounced under HL. This pointed to α-CA4 implication in the processes leading to energy dissipation in PSII antenna. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…The exact position of β-CA5 in Arabidopsis chloroplasts is unknown, but it cannot be excluded that there are two forms of this enzyme with one located in the chloroplast envelope (see above) and the other situated in the thylakoid lumen. The expression level of the At4g33580 gene encoding β-CA5 is 2-3 orders lower than that of, for example, the At3g01500 gene encoding stromal β-CA1 in plants grown at atmospheric CO 2 concentration in low-light conditions [135]. The transcription intensity of the gene encoding β-CA5 was higher when illumination decreased both in short-day and long-day conditions.…”
Section: Ca In the Thylakoid Lumenmentioning
confidence: 86%
See 3 more Smart Citations
“…The exact position of β-CA5 in Arabidopsis chloroplasts is unknown, but it cannot be excluded that there are two forms of this enzyme with one located in the chloroplast envelope (see above) and the other situated in the thylakoid lumen. The expression level of the At4g33580 gene encoding β-CA5 is 2-3 orders lower than that of, for example, the At3g01500 gene encoding stromal β-CA1 in plants grown at atmospheric CO 2 concentration in low-light conditions [135]. The transcription intensity of the gene encoding β-CA5 was higher when illumination decreased both in short-day and long-day conditions.…”
Section: Ca In the Thylakoid Lumenmentioning
confidence: 86%
“…Since the energy-dependent quenching (the part of the NPQ that is associated with the accumulation of protons in the thylakoid lumen) is the main process, which had the effect on changes in NPQ , we suggested that α-CA4 is involved in the protonation of either PsbS protein or violaxantin deepoxidase. The role of α-CA4 in NPQ in PSII antenna was confirmed by the fact that the knockout of the At4g20990 gene affected both the protein content of the light-harvesting complex PSII and the expression level of the genes encoding these proteins [135]. The content of the major PSII antenna proteins, Lhcb1, and Lhcb2 was lower in α-CA4 knockouts than in the WT plants.…”
Section: Ca In Granal Thylakoid Membranesmentioning
confidence: 87%
See 2 more Smart Citations
“…αCa1 is expressed in chloroplasts and αCA2 is expressed in the plasma membrane. α-CA4 is implicated in the processes leading to energy dissipation in the PSII antenna [ 154 ]. Arabidopsis αCA8 is clearly a pseudogene since it encodes in-frame stop codons [ 147 ].…”
Section: Formation and Use Of Bicarbonate In Plantsmentioning
confidence: 99%